Distribution of Lithuanian publications by J. Zavadzkis firm 1805-1864 - Aušra Navickienė (Knygotyra)
J. Zavadzkis' firm—one of the largest printing, publishing, and distributing firms in Lithuania—was the most important enterprise in the publishing and trade of Lithuanian books in the 19th century. The extent of the Zavadzkis family's trade in Lithuanian books directly depended on the publishing activity of the firm. The passive publication of Lithuanian books in the period of 1805-1852 resulted in a minimal extent of Lithuanian books sold. It didn't reach 1% of book sales during the period described.